2004
DOI: 10.1093/brain/awh260
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of a myelin oligodendrocyte glycoprotein-induced demyelinating disease in LEW.1AV1 rats

Abstract: Although multiple sclerosis is considered to be an autoimmune disease in the CNS, the immune responses that take place in the CNS and lymphoid organs remain to be elucidated. Here, we have successfully induced various subtypes of experimental autoimmune encephalitis (EAE) in LEW.1AV1 rats carrying RT1(av1) on the Lewis background genes by immunization with recombinant rat myelin oligodendrocyte glycoprotein (MOG) in various solutions with adjuvants. The purpose of the present study was to analyse in more detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…In addition, the animals harbored a MOG-IgG1 directed humoral immune response [19]. Several studies demonstrated the induction of an NMO-like disease in distinct rat strains following immunization with MOG [21-23]. However, at present only limited information is available regarding MOG-IgG antibodies in human patients suffering from NMO or HR-NMO symptoms and related disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the animals harbored a MOG-IgG1 directed humoral immune response [19]. Several studies demonstrated the induction of an NMO-like disease in distinct rat strains following immunization with MOG [21-23]. However, at present only limited information is available regarding MOG-IgG antibodies in human patients suffering from NMO or HR-NMO symptoms and related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the animals were found to exhibit highly positive serum MOG-IgG1 antibodies [19]. Additionally, there are several reports demonstrating the induction of an NMO-like disease following immunization of certain rat strains with MOG [21-23]. …”
Section: Introductionmentioning
confidence: 99%
“…LEW.1AV1 rats immunized with MOG developed relapsingā€remitting (not depicted) or secondary progressive (Fig. 1A) EAE, both of which are chronic in nature (Sakuma et al,2004). Immunization of LEW rats with MBP induced acute monophasic EAE with relatively constant onset and recovery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pertussis vaccine has been shown to be an adjuvant for the induction of a number of autoimmune diseases. In the animal model of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), the Bordetella pertussis vaccine and pertussis toxin are used to increase disease incidence and severity when administered simultaneously with the autoimmune challenge [3][4][5]. It is suggested that the pro-inflammatory activity of Bordetella pertussis is mainly attributed to an increased permeabilization of the blood-brain barrier leading to an influx of immune cells into the CNS [6].…”
Section: Introductionmentioning
confidence: 99%